2010
DOI: 10.1007/s10295-010-0814-6
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis of S. cerevisiae growth recovery after a sublethal heat-stress applied during an alcoholic fermentation

Abstract: Interest in bioethanol production has experienced a resurgence in the last few years. Poor temperature control in industrial fermentation tanks exposes the yeast cells used for this production to intermittent heat stress which impairs fermentation efficiency. Therefore, there is a need for yeast strains with improved tolerance, able to recover from such temperature variations. Accordingly, this paper reports the development of methods for the characterization of Saccharomyces cerevisiae growth recovery after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In addition, it was demonstrated that the ISM resolved different morphologies in an industrially used yeast strain, thereby providing a basis for future studies of morphological features related to reagent-free cell viability classification (Wei et al, 2007;Tibayrenc et al, 2011). Morphological features have also been previously successfully exploited to assess the viability of animal cells (Wiedemann et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was demonstrated that the ISM resolved different morphologies in an industrially used yeast strain, thereby providing a basis for future studies of morphological features related to reagent-free cell viability classification (Wei et al, 2007;Tibayrenc et al, 2011). Morphological features have also been previously successfully exploited to assess the viability of animal cells (Wiedemann et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, also previous work on image analysis applied to laboratory yeast samples is based on a homogeneous image background (Costello and Monk, 1985;Huls et al, 1992;Pons et al, 1993;Thomas and Paul, 1996;Tibayrenc et al, 2011). This precondition facilitates the application of standard image-processing operations as for example a threshold operation.…”
Section: Introductionmentioning
confidence: 99%
“…They observed heterogeneity in the strength of stress response in the clonal population tested and stated that this heterogeneity was mainly physiologically based, resulting mainly from asynchronous growth in batch cultures (Attfield et al, 2001). Other recent reports focus on comparative genomic analysis of wild-type yeast strains to identify the major type of genome variability that confers genetic diversity to natural yeast populations (Carreto et al, 2008), the development of single-cell analysis methods to detect cell-to-cell variability upon stress exposure (Tibayrenc et al, 2011), and the contribution of positive and negative epistasis to adaptation and reproductive isolation of S. cerevisiae in low-glucose and high-salt environments (Parreiras et al, 2011). For this purpose, survival of stress-sensitive S. cerevisiae mutants was tested and compared with that of the wild type.…”
Section: Evolutionary Engineering Of Stress Resistance In S Cerevisiaementioning
confidence: 99%
“…Similarly, the high heterogeneity of our final evolved populations may also provide a survival advantage at high-stress levels. Other recent reports focus on comparative genomic analysis of wild-type yeast strains to identify the major type of genome variability that confers genetic diversity to natural yeast populations (Carreto et al, 2008), the development of single-cell analysis methods to detect cell-to-cell variability upon stress exposure (Tibayrenc et al, 2011), and the contribution of positive and negative epistasis to adaptation and reproductive isolation of S. cerevisiae in low-glucose and high-salt environments (Parreiras et al, 2011). The high level of heterogeneity of the final evolving populations in our studies might also have resulted from the negative epistasis of different mutations, which individually confer an increased fitness in those evolving populations.…”
Section: Evolutionary Engineering Of Stress Resistance In S Cerevisiaementioning
confidence: 99%
“…Apart from affecting the cells' metabolism, dynamic cultivation conditions impose metabolic stresses on cells and create inherent population heterogeneity (Carlquist et al, 2012; Ackermann, 2015). Consequently, averaged response values fail to describe the influence of different subpopulations and may even mask important characteristics of single cells in a bioprocess (Díaz et al, 2010; Fernandes et al, 2011; Tibayrenc et al, 2011; Gonzalez-Cabaleiro et al, 2017).…”
Section: Introductionmentioning
confidence: 99%